Development of PISA-Like Mathematics Tasks Design of Change and Relationship Content to Measure Mathematical Representation Skills - Suparman, Suparman; Aini, Noor (Asian Journal of Assessment in Teaching and Learning, 2019)
The low ability of students to solve PISA math problems can be seen from the results of the PISA study published by the OECD, 2015 placing Indonesia in position 63 of 70 countries. Therefore, it is necessary to develop PISA math problems, especially in change and relationship content to improve mathematical representation skills. This research is a type of development research by adapting the Tessmer development model. This research was conducted in two stages, namely the preliminary stage, namely preparation and design, then the formative evaluation phase which included self evaluation, prototyping, small group, and field tests. This research is limited to the prototyping. The subjects of this study were students of SMK Diponegoro Depok, Indonesia. The instrument of data collection consists of observation guidelines, interview guidelines, documentation sheets, and questionnaires. Data is analyzed by qualitative techniques. This study produced PISA-like mathematics tasks that were suitable for the needs of students in the era of globalization. This question is designed to measure the ability of mathematical representation. This research can be expanded at the development stage of small group dan field test. This study aims to analyze the needs of developing the PISA-like mathematics tasks of change and relationship content.